(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Employees’ performance is a process supporting the use of human resource in an organization. It is possibly management’s most powerful tool in controlling performance and productivity of human resources in the organization. Used effectively, employees’ performance can have tremendous strategic potential for governing employee behaviour and, in turn, organization’s direction through its dynamic links to selection, training, career path planning and reward system.